The Role of WhatsApp Social Media in Increasing Learning Motivation for Islamic Religious Education during the Covid 19 Pandemic - Fauziah, Fauziah; Tarihoran, Naf’an (Jurnal Ilmiah Wahana Pendidikan, 2024)
The motivation behind this study stemmed from an incident that took place at Darul Huda Mandalawangi Pandeglang Middle School. The objective of this study is to investigate the impact of social media WhatsApp on enhancing students' enthusiasm to acquire Islamic religious education during the Covid-19 pandemic at Darul Huda Middle School Mandalawangi Pandeglang. The research methodology employed in this study is a quantitative approach that utilises surveys and data collection procedures through the administration of questionnaires. The target population for this research consists of students enrolled in grades VII, VIII, and IX, amounting to a total of 320 students for the academic year 2019/2020. A total of 57 pupils were included in the sample, which was selected using random sampling techniques. Based on the computed correlation coefficient of 1%, the resulting value is 0.345. It is evident that the correlation coefficient rxy, which equals 0.921, significantly exceeds the correlation coefficients rtable, which are 0.266 and 0.345. This finding demonstrates a notable correlation between variable X and variable Y.